Aerosolized liposomal amphotericin B for treatment of pulmonary and systemic Cryptococcus neoformans infections in mice. - Gilbert, B E (1992)
Cryptococcus infections of the lung and central nervous system have become major problems in immuno-compromised patients, leading to the need for additional treatment protocols. We have utilized a Cryptococcus-mouse model that mimics human cryptococcal disease to evaluate the efficacy of amphotericin B-liposomes (AmpB-Lip) when delivered by small-particle aerosol (SPA). In the model, initial intranasal inoculation leads to a pulmonary infection that spreads after 2 to 3 weeks to distant organs, including the brain. Aerosols of AmpB-Lip that were generated by a Collison nebulizer had mass median aerodynamic diameters of 1.8 microns and contained 10.3 micrograms of AmpB per liter. When AmpB-Lip SPA was begun at 24 h postinoculation, a single 2-h treatment (0.3 mg of AmpB per kg of body weight) was effective in reducing pulmonary Cryptococcus infection. This regimen was more effective than intravenous administration of AmpB-Lip given for 3 continuous days. This single 2-h exposure to AmpB-Lip also was effective in reducing pulmonary Cryptococcus infection when treatment was delayed for 7 or 14 days. At day 21, when organisms had spread to the brain in all animals, the single 2-h aerosol treatment reduced the number of cryptococci in the brain as well as in the lungs. AmpB-Lip SPA administered once for 2 h on days 7, 14, and 21 also was effective in increasing the duration of survival of infected animals. These results demonstrate that aerosolized AmpB-Lip can be effective in treating both local, pulmonary Cryptococcus disease and systemic disease.